Diffusion Tensor Imaging of Neurofibromatosis Bright Objects in Children with Neurofibromatosis Type 1. Issue 5 (October 2014) - Ertan, Gulhan; Zan, Elcin; Yousem, David M.; Ceritoglu, Can; Tekes, Aylin; Poretti, Andrea; Huisman, Thierry A.G.M.
Neurofibromatosis bright objects (NBOs) are poorly understood. This article aimed to investigate: 1) differences in fractional anisotropy (FA) between NBOs based in gray matter (GM) and white matter (WM), and 2) the relationship between NBOs and the affected white matter tracts. Fourteen NF1 patients were included in this study. Apparent diffusion coefficient (ADC), FA, radial diffusivity (RD) and eigenvalues were used to compare NBOs and matching contralateral normal-appearing sites (NAS). Diffusion tensor imaging scalars were also compared with age-matched healthy controls. Fiber tractography was performed to assess NBO-induced changes in WM trajectories. ADC values were higher for GM and WM NBOs than for NAS and controls. FA values were lower in GM and WM NBOs compared with controls. In all regions, eigenvalues were higher in NBOs than in NAS and controls. Only three out of 18 NOBs appeared to disrupt WM tracts. ADC, Λ2 and RD values of WM NBOs were higher in symptomatic compared to asymptomatic patients. Increased ADC, RD and eigenvalues and decreased FA values in NBOs can be explained by myelin and axonal damage. Increased ADC values and RD in WM NBOs correlated with the presence of symptoms. Tract integrity predominated in our study.